The effects of interventional mitral valve repair using the MitraClip System on the results of pulmonary function testing, pulmonary pressure and diffusing capacity of the lung - Kretzler, Lucie; Große, Stephan; Wiedemann, Stephan; Wunderlich, Carsten; Nowak, Chris; Riedel, Christian; Sieger, Tomáš; Schoen, Steffen (BMC cardiovascular disorders, 2021)
BACKGROUND: The study analyzes changes in lung function, pulmonary pressure and diffusing capacity of the lung in patients with mitral valve regurgitation (MR) treated by MitraClip implantation. METHODS: A total of 43 patients (19 women and 24 men with an average age of 78.0 ± 6.6 years) who were able to perform pulmonary function testing including diffusing capacity of the lung for carbon monoxide (DLCO), vital capacity (VC), total lung capacity (TLC), residual volume (RV) and forced expiratory volume in 1 s (FEV1) before and 6 weeks after MitraClip implantation participated in this study. Furthermore, clinical and echocardiographic parameters including systolic pulmonary artery pressure (sPAP), left ventricular ejection fraction (LVEF) and left atrial diameter (LAD) measurements were recorded in all patients. RESULTS: The procedure was performed successfully in all 43 patients leading to a reduction of MR in 97.7% of cases. One patient died on day 4 after the intervention most likely due to pulmonary artery embolism. Six weeks after the implantation 79.1% of patients showed a MR of at most mild to moderate. Furthermore, we could demonstrate a significant reduction of systolic pulmonary artery pressure during follow-up (from 48.8 ± 11.4 mmHg to 42.9 ± 9.0 mmHg (t(41) = - 2.6, p = 0.01). However, no changes in LVEF were detected. Comparing pre and post implant lung function tests, no significant alterations were seen for VC, TLC, DLCO and FEV1. Though, in a subgroup of patients with moderate to severe preexisting deterioration of DLCO at the baseline (max. 50%) the MitraClip procedure resulted in a significant improvement in DLCO (37.8% ± 9.0 to 41.6% ± 10.0, p < 0.001). CONCLUSIONS: Treatment of MR with the MitraClip system successfully reduces MR severity in the vast majority of patients. Consecutively, a reduction in pulmonary pressure could be observed, however no changes in LVEF were obvious. Lung function tests remained unaltered during follow-up. However, in a subgroup of patients with severe preexisting deterioration of DLCO the MitraClip procedure resulted in a significant improvement in DLCO. TRIAL REGISTRATION: Name of the registry: Die Auswirkung der interventionellen Mitralklappenreparatur mit MitraClip-System auf die Ergebnisse der Lungenfunktionsmessung. TRIAL REGISTRATION NUMBER: DRKS00022435; Date of registration: 09/07/2020 'Retrospectively registered'; URL of trial registry record: https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00022435 .
Keywords: Female; Lung; MitraClip; Prosthesis Design; Heart Valve Prosthesis Implantation; Pulmonary Diffusing Capacity; mitrální insuficience; arteria pulmonalis; protézy - design; ženské pohlaví; výsledek terapie; Cardiac Catheterization; srdeční chlopně umělé; chirurgická náhrada chlopně; Registries; časové faktory; Time Factors; lidé; Pulmonary Artery; Heart Valve Prosthesis; Recovery of Function; Treatment Outcome; Aged, 80 and over; stupeň závažnosti nemoci; obnova funkce; prospektivní studie; Male; Aged; Prospective Studies; Patient registry; Valvular disease; Mitral Valve; mitrální chlopeň; plíce; difuzní kapacita plic; srdeční katetrizace; registrace; senioři nad 80 let; Arterial Pressure; senioři; mužské pohlaví; Severity of Illness Index; Pulmonary function; Structural intervention; arteriální tlak; Mitral Valve Insufficiency; Humans